2018
DOI: 10.5897/ajb2017.16257
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of powdered and ethanolic extracts of Uvaria chamae (Annonaceae) Bark on selected stored product insect pests

Abstract: A study was carried out on the insecticidal effects of the powdered stem bark extract of Uvaria chamae and its ethanolic extract on three most devastating stored products pests (Coleopterous) in Nigeria, namely: Callosobruchus maculatus F. (Bruchidae), Rhizopertha dominica F. (Bostrichidae) and Sitophilus zeamais Motschulsky (Curculionidae). Graded concentrations of each formulation of the powdered bark and ethanolic extracts were in exposure chambers of each insect in laboratory bioassays under ambient condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…The gas chromatogram showed the relative concentrations of various compounds getting eluted as a function of retention time. The heights of the peak indicate the relative concentrations of the compounds of the components present in the plant extracts (Arjun et al, 2012;Negbenebor et al, 2018). Identification of the bioactive compounds was carried out by comparison of their mass spectra and retention time with those of reference standard and published data (Arjun et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The gas chromatogram showed the relative concentrations of various compounds getting eluted as a function of retention time. The heights of the peak indicate the relative concentrations of the compounds of the components present in the plant extracts (Arjun et al, 2012;Negbenebor et al, 2018). Identification of the bioactive compounds was carried out by comparison of their mass spectra and retention time with those of reference standard and published data (Arjun et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The insecticidal effects of the powdered stem bark extract of Uvaria chamae and its ethanol extract was evaluated on three most devastating stored products pests (Coleopterous) in Nigeria, namely: Callosobruchus maculatus F. (Bruchidae), Rhizopertha dominica F. (Bostrichidae) and Sitophilus zeamais Motschulsky (Curculionidae). It was shown that U. chamae powdered and ethanol stem bark extracts have potentials for use during storage of grains, ensuring food security, profit maximization and availability of seeds for the next planting season without being damaged by these test insect species which may be the responsibility of the presence of high concentration of steroids and terpenes (Negbenebor et al, 2018).…”
Section: Insecticidal Activitymentioning
confidence: 99%